2014
DOI: 10.15835/nbha.42.2.9647
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Potential of 1-Methylcyclopropene Treatments to Maintain Fruit Quality of the Common Fig (<i>Ficus carica</i> L. cv. ‘Bursa Siyahi’) during Refrigerated Storage

Abstract: The fig fruit is a unique, climacteric, highly perishable subject to rapid physiological breakdown. Application of 1-methylcyclopropene (1-MCP) was tested to delay ripening of black fig (Ficus carica L. cv. 'Bursa Siyahi') during storage over two growing seasons. Fruits were pre-cooled to 1 °C for 6 hours and afterwards treated with 500 or 1000 nl l -1 of 1-MCP for 24 hours. Treated fruits were stored for 10 days at 1 °C, 90-95% RH and then evaluated. 1-MCP treatments showed that ethylene production, respirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 26 publications
(37 reference statements)
4
9
0
Order By: Relevance
“…Obtained results of 1-MCP goes on line with those of Valdés et al, (2009) and Mu˜noz-Robredoa et al, (2012) in treated apricot and peaches , Yu et al, (2017) in nectarines and Ozkaya et al, ( 2014) in fig. Also, the previous studies reported that AVG significantly slowed the softening rate for apricot (Palou and Crisosto, 2003;Valdés et al, 2009 andMu˜noz-Robredoa et al, 2012), and pears (Tarabih, 2014 andD'Aquino et al, 2010).…”
Section: Fruit Physical Characteristicssupporting
confidence: 87%
See 4 more Smart Citations
“…Obtained results of 1-MCP goes on line with those of Valdés et al, (2009) and Mu˜noz-Robredoa et al, (2012) in treated apricot and peaches , Yu et al, (2017) in nectarines and Ozkaya et al, ( 2014) in fig. Also, the previous studies reported that AVG significantly slowed the softening rate for apricot (Palou and Crisosto, 2003;Valdés et al, 2009 andMu˜noz-Robredoa et al, 2012), and pears (Tarabih, 2014 andD'Aquino et al, 2010).…”
Section: Fruit Physical Characteristicssupporting
confidence: 87%
“…Similar reduction in fruit weight loss was recorded in 1-MCP treated fig (Ozkaya et al 2014), pears (Mahajan et al, 2010), and sweet cherry (Piazzolla et al, 2015), in addition to AVG treated pears (Tarabih, 2014) and in MeJA treated strawberries (Geransayeh et al, 2015), pomegranate (Zolfagharinasab and Hadian 2007). Meanwhile, Fan et al (2000) and Salvador et al (2003) reported that 1-MCP did not affect apricot and plum fruits weight loss.…”
Section: Fruit Storability Characteristicssupporting
confidence: 58%
See 3 more Smart Citations